Analysis of Factors Influencing School Readiness of Children Aged 5-6 Year - Agussalim, Amirah Aminanty; Rasyid, Nurfajriyanti (Indonesian Journal of Educational Studies, 2025)
This study aims to analyze the factors influencing school readiness among children aged 5-6 years in Makassar City. The research employed a quantitative method with a descriptive correlational approach, involving 81 children selected through purposive sampling. The instrument used was the Nijmeegse Schoolbekwaamheids Test (NST), which measures ten domains of school readiness, including cognitive, motor, social, language, and emotional aspects. The results showed that the majority of children (92.5%) were categorized as "ready" to enter primary school, with an average score of 52.95. Visual-perceptual ability and concentration were the strongest domains, while emotional and expressive language abilities were the lowest. No significant differences were found in school readiness between boys and girls. Correlation analysis indicated significant positive relationships among the domains of school readiness, particularly between concentration and memory. These findings confirm that school readiness is a multidimensional construct with interrelated aspects. The results of this study are expected to serve as a basis for developing more effective interventions and educational policies to enhance school readiness among young children in Indonesia.